If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(p + 2) + 5p = 60 Reorder the terms: 7(2 + p) + 5p = 60 (2 * 7 + p * 7) + 5p = 60 (14 + 7p) + 5p = 60 Combine like terms: 7p + 5p = 12p 14 + 12p = 60 Solving 14 + 12p = 60 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 12p = 60 + -14 Combine like terms: 14 + -14 = 0 0 + 12p = 60 + -14 12p = 60 + -14 Combine like terms: 60 + -14 = 46 12p = 46 Divide each side by '12'. p = 3.833333333 Simplifying p = 3.833333333
| 5x-9+7=3 | | 6x+5.4=19 | | 13-(4m+5)=4+2m-14 | | 10=-6.9+a | | 6(6x-1)=41 | | 4+3(2r+-8)=28 | | 2(4-9)-5= | | 2/7v-4/3=-3/2 | | x+(-3)=7 | | 4x+6=12-10x | | 5b+10b=9 | | 5(b-1)=25 | | -6.4=6 | | 135=10x+65 | | 4x(10+6)= | | 2(4-9)+10= | | 40x+51=40x+46 | | 5x-20y=10 | | 2(4-9)+-10= | | 8n+4=8n-24 | | y=4c-3(c+2) | | 7w+5y=-13 | | 2(4-9)= | | 11+3p=5 | | 2(1+-4x)+3=45 | | 11n+2=35 | | -6(x+4)=23 | | x-24=12 | | -5y+11=31y | | 7-(5-8x)=4x+3x | | 2y-7=-12y-6 | | 3x+10y=25 |